2018
DOI: 10.1186/s12863-018-0669-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of inbred lines from Shaan A and B groups for identifying loci associated with maize grain yield

Abstract: BackgroundIncreasing grain yield is a primary objective of maize breeding. Dissecting the genetic architecture of grain yield furthers genetic improvements to increase yield. Presented here is an association panel composed of 126 maize inbreds (AM126), which were genotyped by the genotyping-by-sequencing (tGBS) method. We performed genetic characterization and association analysis related to grain yield in the association panel.ResultsIn total, 46,046 SNPs with a minor allele frequency (MAF) ≥0.01 were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…The superior varieties were the basic materials used to adapt maize production in Shaanxi Province. [32]. Thirty-one maize inbred lines containing four elite inbred lines (PH6WC, PH4CV, Zheng58, and Chang7-2) as controls and other inbred lines selected from the Shaan A and Shaan B heterotic groups that were cultivated at Northwest A&F University were used to assess LN tolerance.…”
Section: Plant Materials and Field Experimentsmentioning
confidence: 99%
“…The superior varieties were the basic materials used to adapt maize production in Shaanxi Province. [32]. Thirty-one maize inbred lines containing four elite inbred lines (PH6WC, PH4CV, Zheng58, and Chang7-2) as controls and other inbred lines selected from the Shaan A and Shaan B heterotic groups that were cultivated at Northwest A&F University were used to assess LN tolerance.…”
Section: Plant Materials and Field Experimentsmentioning
confidence: 99%
“…Therefore, genetic variability related to N-utilization has been investigated in maize, wheat, rice, and spring barley [2,[33][34][35][36]. In the present study, tropical maize lines analyzed possessed high diversity for low-N tolerance compared to studies previously reported [11,37]. Thus, high LNAE inbred lines identified in this study may be an important resource for developing low-N tolerant cultivars.…”
Section: Discussionmentioning
confidence: 56%
“…The reason for this may be that BTL and SR have a lower heritability than EL and FL. According to the LD decay distance reported in previous research, the upstream and downstream 150 kb of the significant SNPs are regarded as associated regions ( Li et al, 2018 ). Associated regions including the same genes were considered as one associated region for each trait.…”
Section: Resultsmentioning
confidence: 99%
“…Two hundred and eight inbred lines were sampled at the 3-leaf stage and the DNA was extracted using a modified CTAB method ( Murray and Thompson, 1980 ). The genotypes were determined using tGBS technology (Dara2bio; LLC, Ames, IA, United States) ( Li et al, 2018 ). Overall, 48,432 SNPs were retained.…”
Section: Methodsmentioning
confidence: 99%